Plastid-to-nucleus communication under hypoxia involves group VII ethylene response factors in Arabidopsis thaliana - Melanie V. Leger-Paul; Tilo Renziehausen; Marlene L. Rauschmayer; David González-Campo; Leopold J. M. Wiens; Joana K. Baumgärtner; Katja Schneider; Charlotte Seydel; Andreas Klingl; Martin Lehmann; Dario Leister; Romy R. Schmidt-Schippers; et al. (Proceedings of the National Academy of Sciences, 2026)
Plants trigger specific changes in gene transcription to acclimate to low-oxygen concentrations. Plastid-localized STEAROYL-ACYL CARRIER PROTEIN ∆9-DESATURASE 6 (SAD6) converts C18:0- into C18:1-fatty acids and belongs to the core hypoxia-responsive genes. SAD6 expression under hypoxia is activated by RAP2.12, which is a group-VII ethylene-response factor (ERF-VII) transcription factor regulated by sequestering to ACYL-CoA BINDING PROTEIN (ACBP) at the plasma membrane or proteasomal degradation via the PLANT CYSTEINE-OXIDASE N-degron pathway in response to molecular oxygen. Besides its role as hypoxia-specific marker gene, the biological function of SAD6 remains unclear. Here, we show that SAD6 overexpression mostly phenocopies plants overexpressing an N-degron insensitive Δ13RAP2.12 protein, which fails to be targeted to proteasomal degradation, while silencing of SAD6 in Δ13RAP2.12 -overexpressor plants largely restores the wildtype phenotype, indicating SAD6 is crucial to shape the growth phenotype of plants with deregulated RAP2.12. However, silencing of SAD6 also attenuated the expression of other important hypoxia-responsive genes, both, in Δ13RAP2.12 -overexpressor and wildtype backgrounds in response to hypoxic treatment, indicating a signaling role of SAD6 in activating RAP2.12. By using green-fluorescent protein-reporter constructs we found that this is due to SAD6 promoting RAP2.12 relocation from the plasma membrane to the nucleus, most likely by its role to increase C18:1-acyl-CoA, which is bound by ACBP as ligand. These results indicate SAD6 to be crucial to trigger relocation of sequestered RAP2.12 protein to the nucleus, showing an involvement of plastid function in hypoxia signaling, which links plastid fatty-acid metabolism with plastid-to-nucleus retrograde signaling via ERF-VII factors to improve hypoxic-stress resistance.